MEASURING HOUSEHOLD ENERGY POVERTY IN BENIN USING BOARDMAN'S ECONOMIC APPROACH - FAGBEMI, LATIF ADÉNIYI; EKOUEDJEN, Evrard Karol; Onibon Doubogan, Yvette; ADAMON, David G. F.; ZANNOU-TCHOKO, Stéphen Junior; JODOIN, Laurent (My University, 2020)
In this paper, energy poverty is measured on households in Benin using Boardman's economic approach. The survey covered a sample of 640 households selected by simple random probability sampling. The households are mainly located in rural and peri-urban areas. The results indicate that out of all the households surveyed, 506 households or 79.06% are in energy poverty. The study also reveals that households living in energy poverty mainly use firewood (76.48%) followed by charcoal (18.18%) as a source of cooking energy. These sources are combined with inefficient or poorly efficient cooking stoves and poorly efficient and expensive lighting energy sources. In fact, the majority of these households use three-stone stoves (67.19%), followed by woodlouse stoves 16.40%). Dry cell flashlights (34.78%) are the main source of energy for lighting, followed by kerosene lamps (24.70%). All these factors combined with the high cost of improved households and low income justify the energy poverty status of households. Household members found to be energy poor report suffering from respiratory health problems (46.05%) and 50% of them suffer from visual health problems.
Keywords: energy poverty; Boardman's economic; approach; survey; households; energy; source; health problems